Dissemination of Class 1, 2 Genes in Extensive Drug Resistant (XDR) Acinetobacterbaumannii Isolated from Clinical Speciemens in Babylon Province, Iraq - Raheem , Haider Qassim (International Journal of Psychosocial Rehabilitation, 2020)
Six hundred samples from Al-Hilla Teaching Hospital and Mirjan Medical City in Babylon Province were composed through the period from October 2018 to February 2019. In addition to the Vitek2 method, twenty A.baumannii isolates were collected as unpolluted and main crops after samples were recognized using morphological properties and biomedical tests. Twenty A.baumannii isolates, as calculated by the Vitek 2 method. Results indicated that entirely isolates were resistant to at least 3 groups of antibiotics, therefore these isolates were expressed as being (MDR) 20(100 percent) multidrug resistant. Of which 15 isolates (75%) is marke d as XDR However,0(0%) for A.baumannii isolates were not resistant to all existing agents in all the classes of antibiotics tested and therefore PDR isolates cannot be considered. Two sets of primers were examined in all the isolates for the identification of Class 1, 2 Integron resistance genes. Showed positive results 6(30 percent) for Int1 and Int2 4(20 percent) of investigated genes.